Adapting to climate change : an assessment of vulnerability and risks to human security in the Western Mediterranean Basin /: an assessment of vulnerability and risks to human security in the Western Mediterranean Basin. (2017) - Malak, Dania Abdul; McGlade, Katriona; Pascual, Diana; Pla, Eduard
No abstract available